Análisis jurídico y doctrinario del hurto cometido por estado de necesidad, según la sentencia No. 004-18-PJO-CC - Aguilar Veintimilla, Karen Estefanía (2023)
The present Curricular Integration Work entitled: "Legal and Doctrinal Analysis of the theft committed by necessity, according to sentence No. 004-18-PJO-CC", the same one that arises the interest to investigate, since it is evident that there is a procedure to be followed against the person who commits theft out of necessity because the person steals food or medicine to survive because he is in the most extreme need to do so, with this what he seeks is to protect the legal right of the life even though it causes damage that threatens the property. In the national reality in the face of this criminal act, the administrators of justice do not have a clear specification at the moment of proceeding on how to sanction the theft due to necessity, emphasizing that some sanction it as a contravention and others as a crime. Theft committed by necessity is a social problem that entails due to the lack of sources of work, which people, faced with the inequalities of society, are forced to steal, obtaining with this act a sanction of a custodial sentence, causing more problems for society. In the present work of curricular integration, materials and methods were applied that allowed the development of the investigation, likewise, interviews and surveys were carried out with legal professionals, and the results obtained served to be able to know the different problems that arise because of this social reality, allowing the establishment of proactive guidelines that help find the most viable way for the procedure and likewise find the solution of giving a custodial sentence or other precautionary measures in the face of theft committedby necessity.